Reaction study and phase formation in Bi2O3-ZnO-Nb2O5 ternary system - Tan, Kar Ban; Lee, Chnoong Kheng; Zainal, Zulkarnain; Khaw, Chwin Chieh; Tan, Yen Ping; Shaari, H. (Akamai University, 2008)
The formation of two structurally related phases; cubic pyrochlore and monoclinic zirconolite in Bi2O3-ZnO-Nb2O5 (BZN) ternary system was investigated. Phase pure Bi4Zn4/3Nb8/3O14 synthesized via conventional solid state methods at 950oC was refined and fully indexed with space group C2 /c; lattice parameters, a = 13.1109(3) Ǻ, b = 7.6764(2) Ǻ, c = 12.1528(2) Ǻ and α = γ = 90C and β = 101.33o, respectively. Reaction study revealed that Bi5Nb3O15 and BiNbO4 phases are two important precursors that react with ZnO at higher temperatures during phase formation. The pyrochlore does not form at the conventionally predicted composition Bi4Zn4/3Nb8/3O14, which falls in the zirconolite region. Instead, cubic pyrochlore forms at substantially lower Bi concentrations in BZN system. The two interrelated areas, a trapezoidal cubic pyrochlore subsolidus, and a rectangular shaped monoclinic zirconolite subsolidus serve to confirm the data consistency over various phase assemblages and compatibility in the phase diagram.